Sarcomatous Components May Predict Prognosis in Patients with Pulmonary Pleomorphic Carcinoma - Tagawa, Tetsuzo; Morimoto, Junichi; Yoshida, Shigetoshi; Yoshino, Ichiro (The Thoracic and Cardiovascular Surgeon, 2015)
Objectives and Methods Pulmonary pleomorphic carcinoma often presents with clinically aggressive behavior. We retrospectively reviewed 16 patients who underwent surgery from 1999 to 2013.Results Sarcomatous components included spindle cell type in six (38%) patients, giant cell type in three (19%) patients, and mixed cell type in seven (44%) patients. The 5-year overall survival rate was 40.6%. On univariate analysis, spindle cell type, pN0, and small tumor diameter were associated with better prognosis. The 5-year survival of six patients with spindle cell type was 83.3%.Conclusions Despite the small sample size, we suggest that patients with spindle cell type may have favorable prognoses.
Keywords: lung cancer; surgery; sarcoma